1890 Iowa Acts 51 - (:unkn) unknown (My University, 1890)
§ 7: Prohibited placing in any of the state waters any lime, ashes, drug, medicated bait. Also prohibited shooting any gun or using any dynamite, gun cotton, giant powder, or other explosive or any electrical machine to catch fish.
Keywords: FISHING REGULATION